Problematika Orang Kristen Masa Kini Dalam Bingkai Pelayanan Pastoral Konseling - Rezeki Putra Gulo; Agus Mawarni Harefa (Jurnal Pendidikan Agama dan Teologi, 2023)
The decline in the faith of some Christians today is one of the problems that often occurs. The influence of life's struggles which are quite heavy and difficult to resolve, sometimes some church members take alternatives that are not in accordance with God's will. one example is believing in supernatural things (paranormal) rather than trusting God in handling and solving the problem. This study aims to present ideas based on pastoral counseling in responding and providing solutions to problems that often occur in the lives of Christians today. This study uses a qualitative method with a library approach. The final conclusion from the author is that it should be acknowledged and trusted that pastoral counseling is one of the important figures in providing solutions to every spiritual problem that occurs in the lives of Christians today.